2022
DOI: 10.1001/jamapediatrics.2021.4822
|View full text |Cite
|
Sign up to set email alerts
|

Association of County-Level Poverty and Inequities With Firearm-Related Mortality in US Youth

Abstract: IMPORTANCE Youth firearm-related deaths are a public health crisis in the US. The association between county-level poverty and the risk of firearm-related deaths among youth is unknown, however.OBJECTIVE To examine the association between county-level poverty concentration and firearm-related mortality rates in US youth. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study analyzed US firearm fatalities in children and young adults aged 5 to 24 years that occurred between January 1, 2007, and December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 59 publications
(109 reference statements)
3
31
0
Order By: Relevance
“…The increase in firearm fatalities has not been equally distributed geographically in the US. Prior study findings suggest that firearm-related suicides may be more common in more impoverished counties . The maps in our study may serve to demonstrate where interventions may be focused at the state and county level.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The increase in firearm fatalities has not been equally distributed geographically in the US. Prior study findings suggest that firearm-related suicides may be more common in more impoverished counties . The maps in our study may serve to demonstrate where interventions may be focused at the state and county level.…”
Section: Discussionmentioning
confidence: 65%
“…Prior study findings suggest that firearm-related suicides may be more common in more impoverished counties. 24 , 25 , 26 , 27 The maps in our study may serve to demonstrate where interventions may be focused at the state and county level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple indicators (e.g., income inequality, unemployment, and housing and economic instability) are associated with risk for homicide and suicide ( 3 5 ). Youth firearm homicide and suicide rates have been associated with poverty at the county level ( 6 ), and the percentage of youths living in conditions of household poverty is higher among racial and ethnic minority populations ( 6 ). The economic and social challenges associated with the COVID-19 pandemic could have exacerbated such risks ( 2 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…But, some studies showed opposite findings [ 17 , 44 ]. Some studies, that analized the impact of the Australian Gun Buyback program and the Australian National Firearms Agreement on suicide mortality rates in the Australian population, showed that there was no statistically observable additional impact on suicide mortality attributable to firearms [ 45 , 46 ]. Consequently, although most researchers agree that there is evidence for the effectiveness of restricting access to firearm in prevention of suicide, the above studies suggest that a much more dimensional strategy to reduce firearm-related suicide deaths is needed.…”
Section: Discussionmentioning
confidence: 99%